HIGH SCHOOL CHOICES AND THE GENDER GAP IN STEM. (25th September 2020) - Card, David; Payne, A. Abigail
Abstract : Women are less likely than men to graduate with a degree in science, technology, engineering, or math (STEM). We use detailed administrative data for a recent cohort of Ontario high school students, combined with data from the province's university admission system, to analyze the sources of this gap. We show that entry to STEM programs is mediated through an index of STEM readiness that depends on end‐of‐high school courses in math and science. Most of the gender gap in STEM entry can be traced to differences in the share of college entrants who are STEM‐ready; only a small share is attributable to differences in the choice of major conditional on readiness. We then use high school course data to decompose the gender gap in STEM readiness into two channels: one reflecting the gap in the fraction of high school students with the necessary prerequisites to enter STEM, the other arising from differences in the overall fractions of females and males who enter university. The gender gap in the fraction of males and females with STEM prerequisites is small. The primary driver of the gap in STEM readiness is the low rate of university entry by nonscience‐oriented males. ( JEL I21, 28, I20)